Apoptosis and Autophagy: regulatory connections between two supposedly different processes - Thorburn, Andrew (2008)
Apoptosis and autophagy are genetically-regulated, evolutionarily-conserved processes that regulate cell fate. Both apoptosis and autophagy are important in development and normal physiology and in a wide range of diseases. Recent studies show that despite the marked differences between these two processes, their regulation is intimately connected and the same regulators can sometimes control both apoptosis and autophagy. In this review, I discuss some of these findings, which provide possible molecular mechanisms for crosstalk between apoptosis and autophagy and suggest that it may be useful to think of these processes as different facets of the same cell death continuum rather than completely separate processes.